2016
DOI: 10.1186/s13054-016-1431-1
|View full text |Cite
|
Sign up to set email alerts
|

The usability of ventilators: a comparative evaluation of use safety and user experience

Abstract: BackgroundThe design complexity of critical care ventilators (CCVs) can lead to use errors and patient harm. In this study, we present the results of a comparison of four CCVs from market leaders, using a rigorous methodology for the evaluation of use safety and user experience of medical devices.MethodsWe carried out a comparative usability study of four CCVs: Hamilton G5, Puritan Bennett 980, Maquet SERVO-U, and Dräger Evita V500. Forty-eight critical care respiratory therapists participated in this fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
1
31
0
2
Order By: Relevance
“…Our usability study of ventilator user-interface showed that most ventilators now used in China have poor ergonomics, with high task error rates (21.2% to 35.0%) and longer task completion times than those reported in published studies [ 17 – 21 ]; this can lead to serious consequences in emergency situations. These can be illustrated by several examples observed in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Our usability study of ventilator user-interface showed that most ventilators now used in China have poor ergonomics, with high task error rates (21.2% to 35.0%) and longer task completion times than those reported in published studies [ 17 – 21 ]; this can lead to serious consequences in emergency situations. These can be illustrated by several examples observed in our study.…”
Section: Discussionmentioning
confidence: 82%
“…For example, an HF evaluation of critical care ventilators found that one ventilator model demonstrated higher levels of safety and user experience compared with the other three models evaluated. The results of this evaluation can support ventilator purchasing decisions . Another HF evaluation of two automated chest compression devices found that the interruption in chest compressions when applying either device to the patient was notably longer than the maximum interruption time recommended by the American Heart Association.…”
mentioning
confidence: 77%
“…The results of this evaluation can support ventilator purchasing decisions. 7 Another HF evaluation of two automated chest compression devices found that the interruption in chest compressions when applying either device to the patient was notably longer than the maximum interruption time recommended by the American Heart Association. The results of this evaluation prevented the purchase of an automated chest compression device at the authors' health care facility.…”
Section: Edical Devices (Eg Electrosurgical Units [Esus])mentioning
confidence: 99%
“…The task will mainly involve a pilot run of the main experiment with think-alouds and unstructured interviews. We will recruit approximately 12 experienced respiratory therapists [ 10 ] and instructors from the respiratory therapy program at Conestoga College. The pilot trial and feedback will be used to make modifications in the materials.…”
Section: Methodsmentioning
confidence: 99%
“…However, the model focuses on the evaluation of medical terminology rather than user interface(s) incorporating a given terminology, and the model does not prescribe a protocol for comparing several systems that incorporate alternative terminologies [ 9 ]. Morita et al [ 10 ] reported a study comparing the safety and user experience of four ventilator models; although their experimental protocol is informative for usability studies involving ventilators, their design is not concerned with nomenclature standardization. Therefore, our protocol to evaluate the usability of a standardized nomenclature applicable across user interfaces of several heterogeneous devices would be a contribution, and the protocol would be applicable in other terminology-related usability studies.…”
Section: Introductionmentioning
confidence: 99%